The construction of a model for lean product development - Khan, Muhammad Sharjeel (Cranfield University, 2012)
‘Lean’ or ‘lean thinking’ refers to an improvement philosophy which focuses on the fulfilment of customer value and the reduction of waste. This philosophy is credited with the extraordinary rise of Toyota, one of the largest and most profitable automotive companies in the world. This thesis presents a pioneering study investigating how lean thinking should be applied to product development (PD). The aim of the research was to construct an innovative model which supports the implementation of lean thinking in PD. This was achieved through progressive collaboration with practitioners from European manufacturing companies. The model provides a process for the conceptual development of an engineering project, and is composed of phases and activities for which methodologies have been defined. The construction of the lean PD model was preceded by a systematic literature review and an industrial field study, wherein 36 semi-structured interviews were conducted in five manufacturing companies in Europe. The constructed model was later implemented on two real-life case studies via action research. The two conducted case studies involved the product architecture design for a car audio head unit and the development of a helicopter engine. It was concluded that the lean PD model addresses various industrial challenges including customer value, communication, and innovation. Furthermore, by focusing on conceptual design, the lean PD model is expected to reduce design rework. As a result of the positive effects of the model, one of the companies involved intends to implement the lean PD model further, and wishes to extend the model to the rest of the organisation. This research makes four main contributions: (1) a novel lean PD model; (2) a number of tools developed to support the model; (3) a framework for lean PD enablers; and (4) a categorisation of challenges faced by PD in industry used to verify the relevance of the lean PD model.
Keywords: Innovation; set-based; engineering; design; knowledge-based; Toyota